Pre-Service Teachers' Online Teaching Readiness: Validation of Paliwal and Singh's Questionnaire - Sintia Triana; Herri Mulyono (Universitas Pahlawan Tuanku Tambusai, 2022)
The present study aimed to investigate the psychometric characteristic of Paliwal and Singh's questionnaire used to evaluate pre-service teachers' readiness to teach online. Non-probability sampling was used to collect the required data from the participants. Using a suvery design, the study distributed Paliwal and Singh's (Paliwal & Singh, 2021) online questionnaire that was already translated into Indonesian. A total of 116 pre-service teachers took part in this study, but only eighty-eight responses from the participants were analysed due to data appropriateness. Rasch analysis was carried out to examine the unidimensionality aspect, person-item reliability, item statistics, person-item measure, and finally the item-person Wright map. The findings showed that nine-items of OTR developed by Paliwal and Singh questionnaire were valid to collect the data related to online teaching readiness. The Rasch analysis of Online Teaching Readiness revealed that the use of Rasch model to analyze this scale was suitable and produced a high level of reliability both for person and item. Findings of the study also suggest some implications and recommendations for future use of the questionnaire